The cross-cultural suitability analysis of “the Educator Cognitive Sensitivity scale”: Empirical exploration from early childhood teachers - Lu, Beibei; Chen, Dezhi; Yan, Congcong (Frontiers in Education, 2022)
The applicability of the ECS scale is an important prerequisite for promoting teachers’ cognitive sensitivity concepts and research. For this reason, we have expanded the study of the measurement properties of the ECS scale in the Chinese context of early childhood teachers and promote the development and research of cognitive sensitivity of teachers in the context of Chinese culture. The scale was used to evaluate 100 Early childhood teachers from a province in eastern China. The results showed that the internal consistency of the scale was good. The structural validity analysis results of the scale were similar to the existing research results; taking some items in the curriculum promotion of “The Path Towards Excellence—Chinese Kindergarten Education Quality Rating Standards” and children's development scale as the target, the empirical validity analysis results showed that the empirical validity of the scale was not very ideal, which needs further practical exploration in the future.